Toward the Implementation of Circular Economy Strategies: An Overview of the Current Situation in Mineral Processing. (18th August 2022) - Cisternas, Luis A.; Ordóñez, Javier I.; Jeldres, Ricardo I.; Serna-Guerrero, Rodrigo
ABSTRACT: Mining resources have played a leading role in the development of humanity, and the demand for these raw materials is expected to increase in the foreseeable future. In addition, new technologies also require the extraction of new critical materials. These trends pose various challenges as there is a limited supply of natural resources, and standard mining and mineral processing practices are associated with significant environmental impacts, such as waste generation, energy and water consumption, and CO2 emissions. The circular economy (CE) has recently gained attention as a model to address such a complex scenario. This work analyzes the current efforts toward the application of CE in mineral processing. Although advances have been made, this review shows that the most significant material flows and environmental impacts occur near the production sites, which currently limits the closure of loops. Besides, mining industries are conservative regarding the adoption of new technologies or processing strategies, which is another hindrance to the implementation of the CE. Thus, and with few exceptions, while some sectors are already facing advanced stages of CE (namely, CE 3.0), the mineral processing field struggles to advance from the basic CE requirements (i.e, CE 1.0 to CE 2.0).